ANALISIS KEBANGKRUTAN PADA PERUSAHAAN BATUBARA DI BURSA EFEK INDONESIA - Yuliana, Yuliana (Katalogis, 2015)
This research is aimed to analyze financial ratios and the implementation of discriminant analysis in predicting bangkruptcy on coal companies on Indonesian Stock Exchange (IDX) from 2009 to 2013. The method of analysis is Multivariate Discriminant Analysis (MDA) with Simultaneous Estimation method. The research is deskriptif and uses purposive random sampling to determine seven companies. the results reveals that five financial ratios as independent variables have significant value of < 0.05, which means that all variables can be used to predict whether the company is bankrupt or not. The Z-score estimation of coal companies In Indonesia Stock Exchange indicates that four companies are bangkrupt and the other three companies are not bankrupt.